Pregnancy-Related Anemia and Platelet Deficiency Prevalence in the Al-Khums, Libya - Wafa R. Griba; Ahmed A. Algdar; Najla M. Worayet (المجلة الأفروآسيوية للبحث العلمي, 2025)
According to the World Health Organization (WHO), anemia in pregnancy is defined as a hemoglobin concentration below 11 g/dL and is categorized into three levels of severity: mild (10–10.9 g/dL), moderate (9–9.9 g/dL), and severe (below 7 g/dL). Anemia represents one of the most prevalent medical conditions affecting pregnant women worldwide. In Libya, it remains a significant health concern and one of the primary causes of hospital admission among expectant mothers in obstetrics and gynecology departments. This study aimed to determine the prevalence of anemia among pregnant women and its association with platelet deficiency in patients attending the Obstetrics Department at Al-Khums/Souq Al-Khamis Hospital. A total of 50 participants aged 17–46 years were included, and blood samples were collected between February and May 2023 for complete blood count analysis. The results revealed a 60% prevalence of anemia, with the highest rate (63.64%) observed during the third trimester. Thus, 25% of pregnant women exhibited platelet deficiency in the first trimester, while 21.43% had mild thrombocytopenia and 7.14% showed moderate thrombocytopenia.